Desenvolvimento do ofício docente: atividade, (tempo)ral(idade) e saúde - Brito, Mariana Aguiar Alcântara de (2019)
This study departs from the field of worker’s health, focusing on teaching activity, in the context of Federal Higher Education Institution - public IFES and its expansion process. Its general objective is to analyze the profession in its function of sustaining health at work of incoming and late career teachers, facing the transformations of teaching in federal public higher education institutions. A qualitative research, such as research-intervention, was conducted in a course in the humanities area of a public IFES, inspired by the theoretical and methodological approach of the Activity Clinic, with the application of the instructional procedure to the double and simple self-confrontation interviews and crusade with end-ofcareer teachers and newcomers. The data analysis was based on the theoreticalmethodological contribution of Historical-Cultural Psychology and through the interpretative analysis of the discourses and images of the teaching activity, establishing theoretical and empirical analytical categories. The results point to the process of structural precariousness of the teaching career. Paradoxically, all instances of the craft in its tensions were highlighted, calling attention to its characteristics of professional protection through the impersonal instance, the framework of action possibilities built over time by working generations in the generic instance, in the interprofessional debates, which ensure the presence of the interpersonal instance and the openness to stylization and authorial production that makes up the personal instance. Regarding the activities that are part of teaching, the high spot is teaching as a master activity, overvaluing the research in its productivist bias, extension as a constrained activity and management as contingency. Autonomy appears as the hallmark of the craft and as paradox in the face of the institutional control system and the meaning of the work follows the ethical-political service of knowledge construction, suffering, howerver, the transit of affection between an activity and a passivity. The perception of a dangerous scenario is shared at both generational ends. The experience of insecurity and inconsistency in relation to the public service through retirement losses has noticeably affected newcomers, on the other hand, the end-of-career teacher expressively experience the overload and the rupture of social pacts. Understanding teaching as a way of life is emphasized because the relevance teaching activity operates beyond the limits of time and space, which has pointed to a colonization of working time in other social times. In the context investigated, the lack of recognition suffered by the teachers is highlighted, however the presence of the combative style in the dispute for territories was also evidenced. It is concluded that there are wearings in the generic instance resulting from losses in solidarity, however, the craft is reiterated as na instrument of health support, reaffirming the presence of its instances and the creative possibilities of functional migrations. The study aimed to contribute to the development of the teaching profession and the expansion of health potential, by stimulating self-reflection and peer interaction.